Developing a Sourcing Framework for Jaguar Land Rover's Future Microchips - Hdairis, Nadia (2012)
The role technology plays in modern day life has been on the rise for years. However, with the release of smart phones, PC tablets and other cutting edge technologies customers nowadays have much higher expectations in terms of the features they expect to find in their brand new vehicles. Moreover, shorter product life cycles and rapidly changing consumer preferences have forced companies to change the way they do business. More efforts have been put in place to emphasize the need for cost control measures. In addition, purchase planning has been deployed to enhance profitability and achieve a higher market share. As a result, the purchasing function in an organisation has taken a more strategic focus as opposed to its original operational focus. The transition from tactical buying to strategic buying was a mean of ensuring that the company’s purchasing function was aligned with the long-term goals and visions. Hence, the importance of strategic sourcing is not to be underestimated if an organization wishes to thrive in these tough times. The definition of strategic sourcing extends to include the process of selecting the best supplier that can provide Jaguar Land Rover (JLR) with the most competitive costs, quality levels, technologies and service level.